Cinesexuality - MacCormack, Patricia (Queer interventions., 2008)
Cinesexuality explores the queerness of cinema spectatorship - represented as a unique encounter of desire, pleasure and perversion beyond binary dialectics of subject/object and image/meaning. Through a variety of cinematic examples, the book encourages a radical shift to spectatorship as itself inherently queer beyond what is watched and who watches.